Natriuretic Peptide Clearance Receptor (NPR-C) Pathway as a Novel Therapeutic Target in Obesity-Related Heart Failure With Preserved Ejection Fraction (HFpEF) - Egom, Emmanuel Eroume A. (Frontiers in Physiology, 2021)
Heart failure (HF) with preserved ejection fraction (HFpEF) is a major public health problem with cases projected to double over the next two decades. There are currently no US Food and Drug Administration–approved therapies for the health-related outcomes of HFpEF. However, considering the high prevalence of this heterogeneous syndrome, a directed therapy for HFpEF is one the greatest unmet needs in cardiovascular medicine. Additionally, there is currently a lack of mechanistic understanding about the pathobiology of HFpEF. The phenotyping of HFpEF patients into pathobiological homogenous groups may not only be the first step in understanding the molecular mechanism but may also enable the development of novel targeted therapies. As obesity is one of the most common comorbidities found in HFpEF patients and is associated with many cardiovascular effects, it is a viable candidate for phenotyping. Large outcome trials and registries reveal that being obese is one of the strongest independent risk factors for developing HFpEF and that this excess risk may not be explained by traditional cardiovascular risk factors. Recently, there has been increased interest in the intertissue communication between adipose tissue and the heart. Evidence suggests that the natriuretic peptide clearance receptor (NPR-C) pathway may play a role in the development and pathobiology of obesity-related HFpEF. Therefore, therapeutic manipulations of the NPR-C pathway may represent a new pharmacological strategy in the context of underlying molecular mechanisms.